Propofol in combination with remifentanil for cesarean section: Placental transfer and effect on mothers and newborns at different induction to delivery intervals - Liguo Hu; Jianhui Pan; Shantang Zhang; Jinjing Yu; Keqiang He; Shuhua Shu; Ruiting Wang (Elsevier, 2017)
Objective: This study aims to describe the administration of propofol in combination with remifentanil for the induction of general anesthesia during cesarean section (CS). Our aim was to evaluate its impact on the drug concentrations of the maternal and neonatal blood at different induction of anesthesia to delivery (I-D) intervals as well as its effect on newborns. Materials and methods: In this double-blind randomized controlled study, patients undergoing elective CS were administered anesthesia at short (n = 20) or long (n = 20) I-D intervals. Anesthesia was induced with 1 mg/kg propofol and 1 μg/kg remifentanil and maintained by continuous infusion of 3 mg/kg/h propofol and 7 μg/kg/h remifentanil. Results: The mean plasma propofol concentrations at delivery in the maternal arterial (MA) blood and the fetal umbilical arterial (UA) and venous (UV) blood in the short I-D interval group were 1.91, 1.17, and 0.51 μg/mL, respectively, while those in the long I-D interval group were 1.57, 1.07, and 0.61 μg/mL, respectively. The mean plasma remifentanil concentrations at delivery in the MA, UA, and UV in the short I-D interval group were 2.25, 1.43, and 0.65 ng/mL, respectively, and those in the long I-D interval group were 1.96, 1.25, and 0.75 ng/mL, respectively. There were no statistically significant differences in the neonatal Apgar scores and neurological adaptive capacity scores between the two groups. Conclusions: It is safe to administer propofol in combination with remifentanil by continuous infusion after the bolus dose for the induction of anesthesia during cesarean section. Prolonging the I-D interval within a certain limit will not have any significant influence on the fetus.